(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Bioprinting is a relatively new tissue/organ engineering method where living cells with or without biomaterials are printed layer-by-layer in order to create three-dimensional living structures. In comparison to scaffold-based tissue engineering approaches, this method fabricates complex living and non-living biological structures from live cells alone or with biomolecules and biomaterials. This presentation will discuss about direct 3D bioprinting of cell aggregates and also cell-laden hydrogels for tissues/organ engineering. Bioprinting process such as how to digitally copy and design tissue/organs, how to prepare bio-inks, bio-printing instructions and how to print live cells will be explained. The presentation will also discuss the several applications and also the challenges in organ printing.